Properties of Compressed Stabilized Earth Blocks (CSEB) For Low-Cost Housing Construction: A Preliminary Investigation - Waziri, Baba Shehu; Lawan, Zanna Alhaji; Mustapha, Ma'aji Mala (International Journal of Sustainable Construction Engineering and Technology, 2013)
Materials used for the construction of walls are normally required to possess adequate strength and erosion resistance. The study investigates the suitability of stabilized laterite soils for the production of compressed earth blocks for low-cost housing construction. Soil samples for the experiment were obtained at two different locations. Sample I was obtained at a borrow pit along Gujba road in Damaturu Yobe state while Sample II was taken at a borrow pit near lake Alau in Borno sate, Nigeria. The results of the study revealed that the specific gravity, bulk density, moisture content and plasticity index of both samples showed satisfactory performance. Different cement stabilization levels of 0%, 2.5%, 5% and 7.5% were used to prepare the specimens for testing. The blocks were moulded using hand operated CINVA-Ram machine. The maximum compressive strength of 2.48N/mm2 was obtained with stabilization level of 7.5% with sample I at 28 days curing. The strength of the specimens increases with increasing cement content with an average value of 0.35N/mm2. For higher strength requirements different stabilization options can be considered.